A novel methodology for large strain under intermediate strain rate loading. (May 2021) - He, H.; Deng, Q.; Wang, C.X.; Li, J.; Weng, K.X.; Miao, Y.G.
Abstract: Hopkinson bar has already worked to measure mechanical properties of materials under high strain rates, but it fails to conduct intermediate strain rates loading with considerable deformation. Thereby, a methodology is proposed for achieving enough large strains under intermediate strain rates. The experimental system based on it is then constructed: a striker bar with same length as incident bar is selected to generate continuous stress wave loading, and a long polymethylmethacrylate bar is preferred as the transmitted bar to guide and record transmitted signals. Thus, loading stress wave is achievable with a nearly constant amplitude and an infinite loading duration. The involved data interpretations are deduced, and verified both theoretically and experimentally. Its measurement capacity is confirmed by loading a thermoplastic polyurethane, and maximum strains up to 12% and 65% under strain rates of 40/s and 270/s, respectively. Finally, the involved influences and factor sensitivities are analyzed for enough experimental accuracy and extensive measurements. Highlights: Hopkinson pressure bar is modified to perform a large deformation under intermediate strain rate loading. A nearly infinite stress wave is achieved with a stable amplitude. The proposed methodology and deduced formulae are verified theoretically and experimentally. Its measurement capacity is evaluated and extended for high loading specifications.